2003
DOI: 10.1002/app.12166
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance of blends of thermotropic liquid crystalline polymer spheres‐dispersed polycarbonate

Abstract: Liquid crystalline polymer (LCP) blends with a thermotropic LCP dispersed in the form of microspheres is studied to show the role of LCP spheres. Polycarbonate (PC), p-hydroxybenzoic acid-poly(ethylene terephthalate) copolyester, and random styrene-maleic anhydride copolymer are used as the matrix, the dispersed phase, and the compatibilizer, respectively. A scanning electron microscopy observation shows the formation of LCP spheres with improved interfacial adhesion in the injection-molded samples via compati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…It fractured in the character similar to that of rigid‐particle‐filled systems. As reported in our previous article,37 a dispersed LCP phase [a random copolyester of HBA and poly (ethylene terephthalate)] was mainly in the form of spherical droplets in the PC composites. This kind of composite exhibited a yield point and some plastic deformation before final fracture, especially when the interphase between the two components was improved by the addition of a proper amount of compatibilizer.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…It fractured in the character similar to that of rigid‐particle‐filled systems. As reported in our previous article,37 a dispersed LCP phase [a random copolyester of HBA and poly (ethylene terephthalate)] was mainly in the form of spherical droplets in the PC composites. This kind of composite exhibited a yield point and some plastic deformation before final fracture, especially when the interphase between the two components was improved by the addition of a proper amount of compatibilizer.…”
Section: Resultssupporting
confidence: 57%
“…Based on our previous studies on the PC composites with sphere‐dispersed LCP phase,37 the increment of core layer thickness and the heterogeneous distribution of more LCP in the core should have benefitted from the toughness improvement of hybrid composite if the poor adhesion between the LCP and PC matrix was improved. The addition of an appropriate compatibilizer into the blends containing LCP can achieve this goal and benefit from the toughing effects of dispersed LCP phase 42, 43.…”
Section: Resultsmentioning
confidence: 99%
“…When 5 wt % SMA was added, tensile strength increases from 24.8 to 44.0 MPa; interaction parameter increased from −0.06 to 15.32 and adhesive strength from 0.62 to 42.74, indicating better interfacial adhesion at the presence of compatibilizer. Another work in our laboratory showed that SMA could also improve the ability to absorb fracture energy of polycarbonate/LCP blends 43. All the above‐mentioned results show that SMA is an effective compatibilizer for blends containing polyamide and polyester, no matter the dispersed phase is an elastomer or plastic.…”
Section: Resultsmentioning
confidence: 84%
“…The remaining solution containing the LCP residue was then centrifuged so that the residue could be collected and dried [19,20]. The residues were then coated with gold and prepared for observation under the scanning electron microscope (SEM).…”
Section: Characterizationmentioning
confidence: 99%